Jewish settlement and pilgrimages (Aliyah) to Palestine in the first Islamic era (638-1099 AD) [İslâmî dönemde (638-1099) fi̇li̇sti̇n'e yahudi̇ göçü ('Ali̇ya:)] - (:unkn) unknown (My University, 2011)
Aliyah is the immigration of Jews from any territory or country to Palestine with the aspiration of permanent settlement. The State of Israel which was declared in 1948 is a direct result of these migrations, which have been encouraged by the Zionist movement since the 19 th century. This paper focuses on the Jewish immigrations to Palestine and its motives in the pre-modern era, from its Islamic conquest up to the Crusaders' occupation (638-1099). In this time period, the immigration to Palestine did not share any similarities with the modern Zionist motivated immigrations. Because of the fair treatment by the Muslims, the Jews had no reason for any quest for a home land as in modern times. The Jewish immigration to Palestine during this time, besides being for reasons such as pilgrimage, visiting the holy land and a desire to live nearby this area, was mainly for economic reasons. From the 10 th century on, as a result of the socio-economic decline and political instability in the Eastern Islamic world many skilled Jews moved towards the Western Islamic world (Syria, Egypt and North Africa) and thereby Palestine. At that time, the only denomination promoting Jewish immigration to Palestine was the Karaites. The Karaites promoted immigration to Palestine to speed up the coming of the Messiah. At the same time, Rabbinical/Orthodox Jews who constituted the majority of the Jewish population did not have migrations with this objective.
Keywords: Aliyah; Jerusalem; Jerusalem and Jews; Jerusalem During the Islamic Period; Jewish immigration to Palestine; Jews; Palestine; Palestine and Jews; Palestine during the Islamic period; Zionism